SME Financial Governance and Access to Capital in Islamic Microfinance Institutions - Julia Noermawati Eka Satyarin; Muhsin Hariyanto; Syah Amelia Manggala Putri; Puri Tri Nanda; Anisatun Anggraeni (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2022)
Introduction: One of the obstacles faced by MSEs to achieve independence in entrepreneurship is limited working capital. The government through Bank Indonesia has required banks and microfinance institutions to provide working capital to SMEs. However, there are obstacles in its distribution, namely the fulfillment of the requirements for submitting financing related to MSE financial information. There are still many MSEs that cannot provide accurate financial information because they do not carry out financial management properly, such as making financial reports. Meanwhile, fund providers, including Islamic microfinance institutions, require financial information to analyze the customer's ability to repay the financing. Purpose: Knowing how the financial management of MSEs and the obstacles faced in making financial reports, and how MSEs provide financial information to obtain working capital from Islamic Microfinance Institutions. Methodology: This research was conducted with a descriptive qualitative method. The object of this research is the financial reporting of MSEs that are needed by Islamic Microfinance Institutions in making decisions to accept or reject the application for financing by MSEs. The data used are primary and secondary data obtained through interviews, documentation, and observation. Findings: The majority of UMK KSPPS BMT Niten customers do not perform financial management, especially in preparing financial reports. Constraints were faced due to the lack of awareness of MSEs on the importance of financial management, especially in preparing financial reporting, lack of knowledge about financial management, especially in preparing financial reporting, and limited time. KSPPS BMT Niten obtains financial information of prospective UMK customers or financial information of existing UMK customers through direct interviews. Paper Type: Research Article